2022
DOI: 10.18549/pharmpract.2022.1.2601
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Satisfaction toward Drugstore Facilities and Services based on the Good Pharmacy Practice Standard in Thailand

Abstract: Introduction: The Good Pharmacy Practice (GPP) standards in Thailand have been legally implemented for all drugstores since 2014. However, customer satisfaction has not been studied. This research aimed to explore the satisfaction of the customers with the facilities and services received from drugstores under the GPP standards and examine the impact of satisfaction toward each GPP domain on overall satisfaction (OS) and the intention to receive the pharmacy services as the first choice in the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…A study conducted in Thailand revealed that assessing customer’s satisfaction towards GPP is a key requirement to ensure that customer’s needs and expectations are met since the opinion of drugstore customers may not agree with the assessment score applied by policy makers. 32 …”
Section: Strengths and Limitationmentioning
confidence: 99%
“…A study conducted in Thailand revealed that assessing customer’s satisfaction towards GPP is a key requirement to ensure that customer’s needs and expectations are met since the opinion of drugstore customers may not agree with the assessment score applied by policy makers. 32 …”
Section: Strengths and Limitationmentioning
confidence: 99%
“…There are also studies by Nattanee Hasitpanichkul and Viroj Jetsadalak (2014) and Pantira Parinyarux and Kitiyot Yotsombut (2022), which found that customer feedback is positive, it will influence on pharmacy because when customers are satisfied with the products and services received from the pharmacy will affect the frequency of service and sales value also increase. [20][21][22] A study by Hanafi et al (2013) found that knowing the GPP is more likely to comply with GPP. 8 Thus, educating the licensees in the GPP correctly and periodically highlighting important information, will create continuous awareness leading to correct practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Thai community pharmacists have expanded their roles and responsibility to become a prescriber for decades. Thai community pharmacists, therefore, had to make a decision in disease differential diagnosis, drug therapy selection, and independent dispensing without prescription from other health professionals (K. Yotsombut, Sooksai, Sookanakenun, Surapan, & Kittikunnakorn, 2010). This unique practice of Thai community pharmacists was strongly accompanied with the CRC (Kapol, Maitreemit, Pongcharoensuk, & Armstrong, 2008;K Yotsombut et al, 2012).…”
Section: Oral Examinationmentioning
confidence: 99%